Reformasi Sistem Peradilan Militer Indonesia - Tiarsen Buaton; Agustinus Purnomo Hadi; Prastopo Prastopo; Ateng Karsoma; M. Ali Ridho (Jurnal Studi Multidisiplin Ilmu, 2024)
Purpose: Reform of the military justice system (criminal law enforcement) is essentially part of the idea of law reform. Law reform not only includes "legal substance reform" and "legal structure reform", but also "legal culture reform". Therefore, the reform of the military criminal law system must also be accompanied by a renewal of military legal culture, which includes, among others, updating the cultural aspects of legal behavior and legal awareness related to "military culture" and updating the aspects of military legal education/science Methodology: Thus, "legal behavior, legal, science and legal education reform" is also needed. This paper will discuss Military Justice Reform in Indonesia, by conducting a comparative study with existing military justice systems in various countries. Results: This article concludes that the prospect of the position of military justice in Indonesia after the administrative, organizational and financial fields are in the Supreme Court will make military justice better and more independent. Its administration and organization will be better organized in line with other courts.